(untitled) (Indian Journal of Animal Production and Management, 2024)
The present study was conducted on weaned broiler rabbits having similar body weights, which were divided into four groups with ten rabbits in each group for a period of 42 days. The objective was to study the effect of inclusion of mannan oligosaccharides (MOS), oxytetracycline and Tulasi (Ocimum sanctum) supplements in the basal diet on hematology and thyroid hormones in New Zealand white rabbits. The result revealed that the TEC was observed significantly higher (p<0.05) in rabbits supplemented with either oxytetracycline or Tulasi. The Hb and PCV was significantly higher in all three supplemented groups. However, the Thyroid hormones T3, T4 and TSH levels did not differ significantly(P<0.05) in all groups.